2004
DOI: 10.1017/s1355617704101045
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the neural systems that mediate the Paced Auditory Serial Addition Task (PASAT)

Abstract: The paced auditory serial addition task (PASAT), in which subjects hear a number-string and add the two most-recently heard numbers, is a neuropsychological test sensitive to cerebral dysfunction. We mapped the brain regions activated by the PASAT using positron emission tomography (PET) and 15O-water to measure cerebral blood flow. We parsed the PASAT by mapping sites activated by immediate repetition of numbers and by repetition of the prior number after the presentation of the next number in the series. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
24
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 46 publications
7
24
0
Order By: Relevance
“…Our results, showing activation in the dorsolateral prefrontal cortex, right and left superior temporal gyrus, right and left medial frontal cortex, and cerebellum in healthy control subjects, are consistent with the above hypothesis. This distribution is in agreement with previous studies that reported a similar regional activation pattern with PASAT in healthy control subjects (8,21). We observed a pattern of activation in mild-TBI patients different from that in healthy control subjects.…”
Section: Discussionsupporting
confidence: 93%
“…Our results, showing activation in the dorsolateral prefrontal cortex, right and left superior temporal gyrus, right and left medial frontal cortex, and cerebellum in healthy control subjects, are consistent with the above hypothesis. This distribution is in agreement with previous studies that reported a similar regional activation pattern with PASAT in healthy control subjects (8,21). We observed a pattern of activation in mild-TBI patients different from that in healthy control subjects.…”
Section: Discussionsupporting
confidence: 93%
“…These areas of activation are consistent with a previous study using the PASAT [28], and it therefore appears that activity in these brain regions is required for the task we used. These results suggest that working memory is necessary for the PASAT, and that the active inhibition required to filter out the distracting stimuli was impaired in the patients with TBI.…”
Section: Discussionsupporting
confidence: 90%
“…It has been reported that the left superior temporal gyrus, anterior cingulate cortex, and extensive brain regions from prefrontal to parietal cortices are active during the PASAT [28]. In this study, we found significant activity in every ROI except the R-LPFC in healthy subjects, but only in the L-APFC and L-LPFC in patients with TBI.…”
Section: Discussionsupporting
confidence: 54%
“…33 Both the Symbol Digit Modalities Test and Paced Auditory Serial Addition Test correlate with several brain imaging findings such as lesion volume and central cerebral atrophy. [34][35][36] The correlation expectedly increases with disease duration and SPMS subtype reflecting greater disease burden and axonal degeneration. 18 Previous studies also show that NAWM abnormalities, even independent of lesion location, may correlate with cognition response.…”
Section: Discussionmentioning
confidence: 99%